Occupational health risks of pathologists - results from a nationwide online questionnaire in Switzerland - Fritzsche Florian Rudolf; Ramach Constanze; Soldini Davide; Caduff Rosmarie; Tinguely Marianne; Cassoly Estelle; Moch Holger; Stewart Antony (BMC, 2012)
Abstract Background Pathologists are highly trained medical professionals who play an essential part in the diagnosis and therapy planning of malignancies and inflammatory diseases. Their work is associated with potential health hazards including injuries involving infectious human tissue, chemicals which are assumed to be carcinogenic or long periods of microscope and computer work. This study aimed to provide the first comprehensive assessment of the health situation of pathologists in Switzerland. Methods Pathologists in Switzerland were contacted via the Swiss Society of Pathologists and asked to answer an ethically approved, online anonymous questionnaire comprising 48 questions on occupational health problems, workplace characteristics and health behaviour. Results 163 pathologists participated in the study. Forty percent of pathologists reported musculoskeletal problems in the previous month. The overall prevalence was 76%. Almost 90% of pathologists had visual refraction errors, mainly myopia. 83% of pathologists had experienced occupational injuries, mostly cutting injuries, in their professional career; more than one fifth of participants reported cutting injuries in the last year. However, long lasting injuries and infectious diseases were rare. Depression and burnout affected every eighth pathologist. The prevalence of smoking was substantially below that of the general Swiss population. Conclusions The results of this study suggest that more care should be taken in technical and personal protective measures, ergonomic workplace optimisation and reduction of work overload and work inefficiencies. Despite the described health risks, Swiss pathologists were optimistic about their future and their working situation. The high rate of ametropia and psychological problems warrants further study.